Reviewing the Islamisation of acquired human knowledge agenda in the International Islamic University Malaysia - Ahmad Sarkawi, Azila; Abdul Rashid, Khairuddin; Mohamad, Nor Asiah (2015)
In Islam, knowledge is categorised as revealed (al-Qur’an and al-Sunnah) and acquired. Acquired knowledge is a matter of concern since it involves human reasoning. While Islam recognises the use of reason in knowledge construction, the manner and the quality of its use is under scrutiny of the Islamic legal theory (usul al-fiqh) and the procedure of ijtihad (interpretation). Derailment of the knowledge construction from the Islamic prescribed manner gives rise to the Islamisation of the output knowledge. By its virtue, Islamisation of the acquired human knowledge (IoAHK) is a process of tracing the root of the human secular output knowledge or going back to the origin (ta’seel) of the principal sources of knowledge in Islam that is al-Qur’an and al-Sunnah. Nonetheless, knowledge and education is indispensable as education is a process of instilling knowledge in oneself. Thus, the paper reports a desk study on the concept of knowledge construction in Islam through ijtihad and the position of IoAHK within that construction, followed by a review on the IoAHK agenda in the International Islamic University Malaysia (IIUM). Through its wing Center for Islamisation established in May 2012, IIUM has produced policies and guidelines on Islamisation including twenty-two modes of Islamisation. These modes could be a pedagogical approach in any discipline of education; however, the paper proposed the refinement in term of the task-word used and the rearrangement based on the degree of importance and complexity. This IoAHK effort is significant in order to bring back the Islamic legacy of pioneering the Quranic and Sunnah-based knowledge.